Toward a better world : memoirs of a life in international and development economics - Helleiner, Gerald K. (University of Toronto Press : University of Toronto Press, Scholarly Publishing Division, 2018)
Towards a Better World describes the life, times and perspectives of Gerry Helleiner, a Canadian activist and university-based economist, who worked for roughly 40 years with developing countries and international organizations. In his memoir, Towards a Better World, Helleiner, recounts the profound early experiences in Africa that propelled him into a rewarding career devoted to research, advice and teaching in international economics, economic development and global poverty reduction. Describing himself as privileged, Towards a Better World recounts his early life as a young academic, having first landed in Africa in the 1960s for the purpose of research for Yale University. Detailing both successes and setbacks, frustrations and hopes, Helleiner, conveys his often difficult, yet transformative, experiences in Nigeria and Tanzania, missions in Uganda and South Africa, and witnesses the wavering efforts being made towards poverty alleviation in international organisations . Providing lively behind-the-scene accounts of multilateral economic meetings in the 1970s through the 1990s, Helleiner addresses his engagement with economic policymakers, his views often challenging common practice. In Towards a Better World, Helleiner speaks to his early motivation as a young man in Africa, and his lifework as a practicing economist determined to make a positive effort in addressing global poverty.